Cancer Theranostics: Ultra‐Small Iron Oxide Doped Polypyrrole Nanoparticles for In Vivo Multimodal Imaging Guided Photothermal Therapy (Adv. Funct. Mater. 9/2014). (March 2014) - Song, Xuejiao; Gong, Hua; Yin, Shengnan; Cheng, Liang; Wang, Chao; Li, Zhiwei; Li, Yonggang; Wang, Xiaoyong; Liu, Gang; Liu, Zhuang
<x xml:space="preserve">Abstract</x> Polypyrrole (PPy), a NIR‐absorbing conjugate polymer, is used by Z. Liu and co‐workers to coat iron oxide nanoparticles (IONPs), obtaining IONP@PPy core–shell nanoparticles, further modified by polyethylene glycol. On page 1194, the obtained multifunctional nanoparticles are guided by dual‐modal magnetic resonance and photoacoustic imaging for in vivo photothermal therapy, achieving an excellent tumor ablation therapeutic effect in a mouse model. These results promise the use of multifunctional NIR‐absorbing organic–inorganic hybrid nanomaterials for applications in cancer theranostics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>